TINGKAT KESEJAHTERAAN KELUARGA PETANI PADI SAWAH DAN JAGUNG DI DESA MATANI, KECAMATAN TUMPAAN, KABUPATEN MINAHASA SELATAN - Liby Rosany Lampah; Oktavianus ., Porajouw; Gene H. M. Kapantow (AGRI-SOSIOEKONOMI, 2017)
This study aims to compare the level of welfare of farmers who seek in the field of wetland rice and corn farmers in the Village Matani Tumpaan District in South Minahasa. The study lasted from July to September 2017. The data used are primary data collected throught interviews with farmers by purposive sampling taken 15 corn farmers and 15 rice field farmers.The study on farmers’ welfare level is seen from the form of economic and non economic variables enjoyed by respondents based on the criteria of BKKBN covering 5 stages of family welfare indicators. Secondary data is obtained throught documents and research results and library, data and information in village, sub-district and district offices. The result of this research concludes that rice farmers are more prosperous than corn farmers in Matani Village. Tumpaan Subdistrict of South Minahasa Regency. Wet land paddy farmers are included in the stages of the Prosperous Family II (KS II) and Prosperous Family III (KS III) while corn farmers are included in the stage of the Prosperous Family I (KS I).